Analisis Terhadap Arah Dan Tujuan Pendidikan Nasional Pada Rencana Kerja Pemerintah Tahun 2005 – 2025 - Mohamad Samsudin (Al Ashriyyah, 2019)
Indonesian development runs on the foundation of Indonesia's long-term vision, namely the realization of nation-states, modern Indonesia that is safe and peaceful, fair and democratic, and prosperous by upholding human values, independence and unity based on Pancasila and The 1945 Constitution. To realize this, education as a subsystem is one of the important aspects to be considered in its direction and purpose so that education is not merely an aspect of supporting Indonesia's development, but as a locomotive of development itself. Because in reality, education is one aspect of life that is run by being influenced by various external aspects that are interrelated with each other such as political, economic, socio-cultural, defense-security aspects, even ideology has a very strong influence on the continuity of education, and vice versa. This paper aims to find out how the Long Term Development Plan (RPJP) is specifically regarding national education between 2005-2010 and 2010-2025. To achieve this goal, the author uses content analysis research using written documents that have been used as guidelines to determine the direction of the Indonesian government's policy in realizing national development. The results of the research in this paper show that the development of national education in the future is based on the paradigm of developing Indonesian people as a whole. The humanitarian dimension includes the three most basic things, namely: cognitive, affective, and psychomotor. This is based on the desire to realize the education system as a strong and authoritative social institution to empower all citizens of Indonesia to develop into quality human beings so that they are able and proactively respond to the challenges of an ever-changing era.